Neurospora heterokaryons involving a thymidine kinase-positive "Helper": use in storing poorly viable strains or crossing strains of limited fertility - R L Metzenberg; M Sachs (Fungal Genetics Reports, 2002)
Many of the most interesting and useful strains encountered in research readily die in storage and/or are semi-sterile. If such strains are Oak Ridge-compatible, they can be carried and even crossed as heterokaryons with the sterile but vigorous strain from the Griffiths lab, am1 ad-3B cyh-1 (FGSC #4564 - Perkins, Neurospora Newsl. 31: 41-42, 1984).